Dampak Pengembangan Pariwisata Terhadap Peningkatan Kesejahteraan Masyarakat Pada Objek Wisata Lembah Harau Di Kecamatan Harau Kabupaten Lima Puluh Kota - Yulhaslinda, Yulhaslinda; Andriani, Rika (LPPM Universitas Muhammadiyah Sumatera Barat, 2024)
Harau Valley is located between two hills namely, Bukit Jambu and Bukit Rengkok. Harau is one of the beautiful and amazing natural attractions with small hills, stretches of rice fields, waterfalls, rivers, cliffs and natural baths. In Harau there are also several homestays with comfortable lodgings and beautiful views, one of the homestays is Dangau Pittosa. Moreover, at the Harau tourist attraction there are various types of tourist attractions that invite many domestic and foreign tourists. This study aims to find out what potential can be developed in the Harau Valley tourist attraction and what is the impact of the Harau Valley tourism development on people's income in the Harau Valley tourist area. The research methods used are observation, interviews and library research. Where the results of the study show that the potential that can be developed is natural potential, homestays and cafes. The impact of homestays for the community is that they can improve the economy because the presence of homestays and cafes can increase visitors to Harau tourist attractions, jobs, Memories in Sapta Pesona, and introduce and spread Minangkabau culture and customs to domestic and foreign visitors.Keywords: Harau Valley, tourist attraction, homestay